1999
DOI: 10.1039/a808986h
|View full text |Cite
|
Sign up to set email alerts
|

Friedel–Crafts Acylation Reaction using Polymer Supported Aluminium Chloride

Abstract: Friedel^Crafts reactions using polymer supported AlCl 3 are reported and the effect of crosslinking level on ortho:para ratio is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Recently, such catalyst was also found to be effective in Friedel-Crafts acylation [22], sulfonylation [23], tetrahydropyranylation [24] and dithioacetalization [25]. In continuation of our recent work on the use of polymer supported catalyst in organic reactions [26], we found that Ps-AlCl 3 was a good catalyst for the synthesis of DHPMs.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently, such catalyst was also found to be effective in Friedel-Crafts acylation [22], sulfonylation [23], tetrahydropyranylation [24] and dithioacetalization [25]. In continuation of our recent work on the use of polymer supported catalyst in organic reactions [26], we found that Ps-AlCl 3 was a good catalyst for the synthesis of DHPMs.…”
Section: Introductionmentioning
confidence: 73%
“…Aldehydes, which are sensitive to acid such as furfural, were not suitable for carrying out the Biginelli reaction under these conditions ( Table 2, entry 23). Thiourea has been used in a similar way to produce the corresponding thio derivatives of dihydropyrimidinones, which are also of much interest with respect to their biological activities ( Table 2, entries [17][18][19][20][21][22]. Using methyl acetoacetate and acetylacetone instead of ethyl acetoacetate, the desired products were also obtained in high yields ( Table 2, entries 2-3).…”
Section: Resultsmentioning
confidence: 99%
“…PS/GaCl 3 was prepared by addition of anhydrous gallium trichloride to polystyrene (5–7% divinylbenzene) in carbon disulfide under reflux conditions. The loading capacity of the polymeric catalyst obtained by the gravimetric method and checked by the atomic absorption technique was 0.391 mmol GaCl 3 /g of complex beads catalyst . The UV spectrum of the solution of the PS‐GaCl 3 complex in CS 2 showed a new strong band at 470 nm, which is due to the formation of a stable π → p type coordination complex between the benzene rings in the polystyrene carrier with gallium trichloride.…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst was dried in a vacuum oven overnight at 50°C before use. The chlorine content of PS/GaCl 3 was 4.17% analyzed by the Mohr titration method , and the loading capacity of GaCl 3 on the polymeric catalyst or the amount of GaCl 3 complexed with polystyrene was calculated to be 0.391 mmol/g .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, immobilization of FeCl 3 on polystyrene resulted in an increase of the surface area and pore volume, but the reduction of pore diameter, and these results were explained by SEM. [27] SEM images of Ps, Ps-TiCl 4 , and Ps-FeCl 3 were shown in Figure 2. From the image of Ps, the morphology of Ps was smooth ball with many pores on the surface, and it was shown that the surface of Ps-TiCl 4 was dispersed with small amount of TiO 2 particles, which was due to the hydrolysis of TiCl 4 in the preparation process.…”
Section: Resultsmentioning
confidence: 99%